2012
DOI: 10.1063/1.4706564
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cancellation coil for precision magnetic measurements with strong prepolarization field inside shielded environment

Abstract: A miniature and ultralow power search coil optimized for a 20 mHz to 2 kHz frequency range

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The NMR signal is, thus, proportional to B p , which is electrically switched on and off. A stronger B p is, of course, advantageous for obtaining a stronger signal; however, it also creates unwanted side effects, such as the induction of eddy currents on the walls of a magnetically shielded room (MSR) [15][16][17] and flux trapping in superconducting pickup coils [24]. Both effects generate a temporally varying field, which broadens the NMR linewidth and distorts the MR image.…”
Section: Introductionmentioning
confidence: 98%
“…The NMR signal is, thus, proportional to B p , which is electrically switched on and off. A stronger B p is, of course, advantageous for obtaining a stronger signal; however, it also creates unwanted side effects, such as the induction of eddy currents on the walls of a magnetically shielded room (MSR) [15][16][17] and flux trapping in superconducting pickup coils [24]. Both effects generate a temporally varying field, which broadens the NMR linewidth and distorts the MR image.…”
Section: Introductionmentioning
confidence: 98%
“…[6][7][8] In a recent paper by Vesanen et al, 9 where a superconducting B p coil made of ultra-fine niobium filaments in bronze matrix was used in their ultra-low field magnetic resonance imaging (ULF-MRI) system, the authors reported a practical upper limit on B p around 22 mT, above which the superconducting B p coil begins to trap magnetic flux as the B p self-field exceeds its own H c1 0 , pinning the flux inside the superconductor. 5,10 This trapped magnetic flux produced an inhomogeneous remanent magnetic field in the sample space that induces image distortion as well as loss of definition from the suppressed signal.…”
mentioning
confidence: 98%
“…In order to create a stronger B p , various types of B p coils have been used, such as a permanent magnet 1 and coils with the following cooling agents: forced air, 2 water, 3,4 a fluorine-based industrial coolant, 5 liquid helium, 6,7 and liquid nitrogen. [8][9][10][11][12] In spite of these efforts, the strength of B p has been limited to below approximately 150 mT. 3 Increasing the magnitude of the B p has also yielded unwanted effects: flux trapping in the superconducting pickup coil 7 and the generation of eddy currents on the walls of a magnetically shielded room (MSR).…”
mentioning
confidence: 99%